Use of NCM based DNA extraction method for simultaneous detection of citrus mosaic badnavirus and Candidatus Liberibacter asiaticus by duplex PCR - P.W. RAMTEKE and DILIP GHOSH*, MANALI MOTGHARE, PRADEEP KUMAR SHUKLA (Indian Phytopathology, 2017)
Candidatus Liberibactor asiaticus (Ca. Las), a phloem limited, gram negative bacterium is the causal organism of citrus greening disease (Huanglongbing/HLB) whereas citrus yellow mosaic disease is caused by Citrus mosaic badnavirus (CMBV). Both the diseases, singly or as mixed infection in the grove are considered as serious threat to Indian citrus industry. Early diagnosis for these systemic pathogens are essential in order to prevent the spread of these diseases and finally to devise their integrated management strategies. In the present study, a method of simultaneous detection of CMBV and ‘Ca. Las’ was developed using a simple nitrocellulose membrane (NCM) based DNA isolation protocol in three commercially grown citrus cultivars in India, viz. mandarin (Citrus reticulata), sweet orange (Citrus sinensis), and acid lime (Citrus aurantifolia) infected with these pathogens. Citrus tissues were crushed in extraction buffer containing NaOH and EDTA. The crude extract was spotted on NCM and incubation elution was done in nuclease-free water after 30 minute of NCM spotting. Eluted products were taken for simultaneous detection of CMBV and ‘Ca. Las’ using duplex PCR with newly designed primers. The developed protocol was found to be equally sensitive as multistep DNA isolation method and commercially available kit. The protocol is simple, rapid and inexpensive thus can be used for large-scale pathogen indexing of citrus plant samples in orchards and nurseries.